Battery cell and battery
By increasing the adhesion between the diaphragm and pole pieces in battery cells, the issues of curling and warping are mitigated, enhancing cycle life and performance through improved lithium ion transmission and reduced deformation.
Patent Information
- Application Number
- CN202411428222.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2024-12-27
AI Technical Summary
The curling and warping of pole pieces during the rolling process in battery cells lead to issues such as lithium precipitation, black spots, and reduced cycle life, as well as abnormal expansion and deformation, affecting the battery's cycle performance.
Enhancing the adhesion between the outermost diaphragm and the second pole piece by ensuring a peeling force of at least 13 N/m, along with specific size and peeling force configurations for electrode groups, to prevent gaps and deformations, thereby improving lithium ion transmission and reducing lithium precipitation.
The solution effectively reduces curling and warping, enhances cycle life, and improves the battery's cycle performance by maintaining flatness and preventing abnormal expansion.
Smart Images

Figure CN119208860A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery energy technology, and in particular to a battery cell and a battery. Background Art
[0002] With the rapid development of battery technology, people expect mobile phones, computers, tablets and other electronic products to be lighter, thinner and more convenient to carry, which puts higher requirements on batteries. At present, the energy density of batteries is getting higher and higher, so the pole pieces will be rolled to increase the energy density.
[0003] In the battery cell, during the rolling process of the pole piece, the active material will be embedded in the current collector, which can easily cause the pole piece to curl and warp, resulting in black spots and lithium precipitation during the cycle, especially in the negative electrode corresponding to the single-sided area, resulting in a reduction in the battery cycle life. In addition, during the cycle, due to the curling and warping of the pole piece, the distance between the pole pieces is likely to increase, and the battery cell will deform during the cycle, causing abnormal expansion and failure of the battery in the thickness direction, affecting the battery cycle performance. Summary of the invention
[0004] Based on this, the present application provides a battery cell and a battery to solve the problems in the related art such as black spots on the battery cell causing lithium precipitation, abnormal expansion and failure, and affecting the battery cycle life and cycle performance.
[0005] The present application provides a battery cell, comprising a first pole piece, a diaphragm and a second pole piece, wherein a plurality of first pole pieces and second pole pieces are stacked along a first direction, and the diaphragm is disposed between adjacent first pole pieces and second pole pieces;
[0006] The first electrode piece includes a first small electrode piece and a first large electrode piece, the second electrode piece includes a second small electrode piece and a second large electrode piece, the size of the first small electrode piece along the second direction is smaller than the size of the first large electrode piece along the second direction, the size of the second small electrode piece along the second direction is smaller than the size of the second large electrode piece along the second direction, the second direction is perpendicular to the first direction, the first small electrode piece and the second small electrode piece form a first electrode piece group, the first large electrode piece and the second large electrode piece form a second electrode piece group, and the first electrode piece group and the second electrode piece group are stacked along the first direction;
[0007] Along the first direction, the peeling force between the outermost diaphragm and the second pole piece adjacent to the diaphragm is F1, and F1 satisfies: F1 ≥ 13 N / m.
[0008] In a possible implementation, F1 satisfies: F1 ≥ 18 N / m.
[0009] In a possible implementation, the peeling force between the diaphragm and the first pole piece is smaller than the peeling force between the diaphragm and the second pole piece.
[0010] In a possible implementation, the difference between the peeling force between the diaphragm and the second pole piece and the peeling force between the diaphragm and the first pole piece is greater than or equal to 4 N / m.
[0011] In a possible implementation, along the first direction, the difference between the peeling force between the pole pieces in the overlapping area of the second pole piece group and the first pole piece group and the peeling force between the pole pieces in the separately stacked area of the second pole piece group is less than or equal to 50% of the smaller value of the two.
[0012] In a possible implementation, along the first direction, the difference between the peeling force between the pole pieces in the overlapping area of the second pole piece group and the first pole piece group and the peeling force between the pole pieces in the separately stacked area of the second pole piece group is less than or equal to 40% of the smaller value of the two.
[0013] In a possible implementation, the peeling force between the first electrode assembly and the second electrode assembly is F3, and F3 satisfies F3 ≥ 30 N / m.
[0014] In one possible implementation, along the first direction, the peeling force between the outermost diaphragm in the first electrode sheet group and the first and second electrode sheets adjacent to the diaphragm is F4, and the peeling force between the outermost diaphragm in the second electrode sheet group and the second and second electrode sheets adjacent to the diaphragm is F5, and F4 and F5 satisfy: F4 ≥ 13 N / m; and / or F5 ≥ 13 N / m.
[0015] In one possible implementation, along the second direction, the peeling force at each position when the diaphragm and the second electrode are peeled off is a, and the average peeling force between the diaphragm and the second electrode is b. Along the third direction, the peeling force at each position when the diaphragm and the second electrode are peeled off is c, and the average peeling force between the diaphragm and the second electrode is d. The second direction is perpendicular to the first direction, and the third direction is perpendicular to the first direction and the second direction. a, b, c, and d satisfy: 50% b≤a≤150% b; and / or 50% d≤c≤150% d.
[0016] In one possible implementation, the second pole piece includes a second current collector and a second active material layer located on at least one side of the surface of the second current collector, the silicon content of the second active material layer is x, the peeling force between the second pole piece and the diaphragm is y, and x and y satisfy: y≥11*x+13.
[0017] The present application provides a battery, comprising a shell and the above-mentioned battery cell, wherein the battery cell is arranged in the shell.
[0018] In a possible implementation, along the first direction, the outermost first pole piece or the outermost second pole piece is in direct contact with the shell.
[0019] The battery cell and battery provided by the present application can solve the problem of curling and warping of the outermost single-sided electrode sheet in the battery cell by improving the adhesion between the outermost diaphragm of the battery cell and the second electrode sheet so that the peeling force F1 therebetween is ≥13N / m, so that the distance between the first electrode sheet and the second electrode sheet will not have a gap due to curling and warping deformation, resulting in a larger interval at the interface bonding point, thereby increasing the transmission distance of lithium ions, reducing the transmission distance of lithium ions, reducing the problem of black spot lithium precipitation during battery cell cycling, and improving the cycle life of the battery. At the same time, since the adhesion between the diaphragm and the second electrode sheet is increased, the deformation problem of the battery cell during cycling can be reduced, the flatness of the battery cell is improved, and the abnormal expansion in the thickness direction during cycling is reduced, thereby improving the cycle performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, a brief introduction will be given below to the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0021] Figure 1 One of the structural schematic diagrams of the battery cell provided in the embodiment of the present application;
[0022] Figure 2 The second structural schematic diagram of the battery cell provided in the embodiment of the present application;
[0023] Figure 3 The third structural schematic diagram of the battery cell provided in the embodiment of the present application;
[0024] Figure 4 The fourth structural schematic diagram of the battery cell provided in the embodiment of the present application;
[0025] Figure 5 A data chart of a peeling test of a pole piece in a battery cell provided in an embodiment of the present application;
[0026] Figure 6 A structural schematic diagram of a flatness test of a battery is provided for an embodiment of the present application.
[0027] Description of reference numerals:
[0028] 100-battery cell; 10-first pole piece; 11-first small pole piece; 12-first large pole piece; 13-first current collector; 14-first active material layer; 20-diaphragm; 30-second pole piece; 31-second small pole piece; 32-second large pole piece; 33-second current collector; 34-second active material layer; 101-first pole piece group; 102-second pole piece group; 200-battery; 201-housing; 202-ear. DETAILED DESCRIPTION
[0029] In order to make the purpose, technical scheme and advantages of the present application clearer, the technical scheme in the embodiment of the present application will be described in more detail below in conjunction with the drawings in the preferred embodiments of the present application. In the drawings, the same or similar reference numerals throughout represent the same or similar parts or parts with the same or similar functions. The described embodiments are part of the embodiments of the present application, not all of the embodiments. The embodiments described below with reference to the drawings are exemplary and are intended to be used to explain the present application, and should not be construed as limitations on the present application. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present application. The embodiments of the present application are described in detail below in conjunction with the drawings.
[0030] In the description of this application, it should be noted that, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, or it can be an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood according to specific circumstances.
[0031] In the description of the present application, it should be understood that the terms "upper", "lower", "front", "back", "vertical", "horizontal", "top", "bottom", "inside", "outside", etc., indicating orientations or positional relationships, are orientations or positional relationships based on the drawings, and are only for the convenience of describing the present application and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the present application.
[0032] The terms "first", "second" and "third" (if any) in the specification and claims of this application and the above drawings are used to distinguish similar objects and are not necessarily used to describe a specific order or sequence.
[0033] In addition, the terms "comprises," "comprising," and "having," and any variations thereof, are intended to cover a non-exclusive inclusion, for example, a process, method, system, product, or display comprising a series of steps or elements is not necessarily limited to those steps or elements explicitly listed, but may include other steps or elements not explicitly listed or inherent to such process, method, product, or display.
[0034] With the rapid development of battery technology, people expect mobile phones, computers, tablets and other electronic products to be lighter, thinner and more convenient to carry, which puts higher requirements on batteries. At present, the energy density of batteries is getting higher and higher, so the pole pieces will be rolled to increase the energy density.
[0035] In the battery cell, the active material of the pole piece, especially the single-sided pole piece, will be embedded in the current collector during the rolling process, which can easily cause the pole piece to curl and warp, making the adhesion of the pole piece relatively poor, resulting in gaps in the interface bonding, which in turn causes the positive and second pole pieces to be too far apart during the cycle, resulting in a large range of lithium ion movement and the appearance of black spots and lithium precipitation, especially for the negative electrode corresponding to the single-sided area, resulting in a reduction in the battery cycle life.
[0036] In addition, the current battery requirements for energy density are getting higher and higher, and silicon-containing negative electrode materials are generally used. However, during the cycle, the expansion of silicon-containing negative electrode materials is relatively large. At the same time, due to the curling and warping of the pole piece, it is easy to have different thickness areas on the surface of the battery cell, which will deform during the cycle, especially for thin batteries, affecting the flatness of the battery cell. For 3D special-shaped batteries, due to the different sizes of the pole pieces, the battery cycle expansion rate will also be different, which will also cause the battery to deform. In the thickness direction, the battery deforms, causing abnormal expansion and failure of the battery, affecting the battery cycle performance.
[0037] After repeated thinking and verification, the inventors found that if the adhesion between the outermost electrode of the battery cell and the diaphragm is improved, on the one hand, the problem of curling and warping of the electrode can be reduced by increasing the peeling force, and the problem of black spots and lithium plating during battery cycle can be solved, thereby increasing the cycle life of the battery cell, especially the negative electrode corresponding to the single-sided area; on the other hand, it can solve the cycle deformation and abnormal thickness expansion of the battery cell and improve the cycle performance of the battery cell.
[0038] In view of this, the present application provides a battery cell, including a first electrode sheet, a diaphragm and a second electrode sheet. Along a first direction, a plurality of first electrode sheets and second electrode sheets are stacked, and the diaphragm is arranged between adjacent first electrode sheets and second electrode sheets; the first electrode sheet includes a first small electrode sheet and a first large electrode sheet, and the second electrode sheet includes a second small electrode sheet and a second large electrode sheet. The size of the first small electrode sheet along the second direction is smaller than the size of the first large electrode sheet along the second direction, and the size of the second small electrode sheet along the second direction is smaller than the size of the second large electrode sheet along the second direction. The second direction is perpendicular to the first direction, the first small electrode sheet and the second small electrode sheet form a first electrode sheet group, and the first large electrode sheet and the second large electrode sheet form a second electrode sheet group. Along the first direction, the first electrode sheet group and the second electrode sheet group are stacked; along the first direction, the peeling force between the outermost diaphragm and the second electrode sheet adjacent to the diaphragm is F1, and F1 satisfies: F1≥13N / m.
[0039] By improving the adhesion between the outermost diaphragm and the second pole piece of the battery cell and making the peeling force F1 between the two ≥13N / m, the problem of curling and warping of the outermost single-sided pole piece in the battery cell can be solved, so that the distance between the first pole piece and the second pole piece will not have a gap due to curling and warping deformation, resulting in a larger interval at the interface bonding point, which increases the transmission distance of lithium ions, reduces the transmission distance of lithium ions, reduces the problem of black spot lithium precipitation during the battery cell cycle, and improves the cycle life of the battery. At the same time, due to the increased adhesion between the diaphragm and the second pole piece, the deformation problem of the battery cell during circulation can be reduced, the flatness of the battery cell is improved, and the abnormal expansion in the thickness direction during circulation is reduced, thereby improving the cycle performance of the battery.
[0040] The contents of the present application will be described in detail below in conjunction with the accompanying drawings so that those skilled in the art can understand the contents of the present application more clearly and in detail.
[0041] Figure 1 This is one of the structural schematic diagrams of the battery cell provided in the embodiment of the present application. Figure 2 This is the second structural schematic diagram of the battery cell provided in the embodiment of the present application. Figure 3 This is the third structural schematic diagram of the battery cell provided in the embodiment of the present application. Figure 4 This is the fourth structural schematic diagram of the battery cell provided in the embodiment of the present application. Figure 5 A data chart of a peeling test on a pole piece in a battery cell provided in an embodiment of the present application. Figure 6 A structural schematic diagram of a flatness test of a battery is provided for an embodiment of the present application.
[0042] like Figure 1 and Figure 2 As shown, the battery cell 100 provided in the embodiment of the present application is used in a battery. The battery cell 100 includes a first pole piece 10, a diaphragm 20 and a second pole piece 30. Along a first direction x, a plurality of first pole pieces 10, diaphragms 20 and second pole pieces 30 are stacked, that is, the first pole pieces 10 and the second pole pieces 30 are alternately stacked, and the diaphragm 20 is arranged between adjacent first pole pieces 10 and second pole pieces 30. The first direction x is the stacking direction of the battery cell 100.
[0043] In a possible implementation, the battery may be a soft-pack laminated battery, a steel-shell laminated battery, or a wound laminated battery, but is not limited thereto. The battery may also be a combination of other different types of battery cells 100 and different shells.
[0044] In one possible implementation, the first pole piece 10 is a positive pole piece, and the second pole piece 30 is a negative pole piece, but it is not limited thereto. In other possible implementations, the first pole piece 10 may also be a negative pole piece, and the second pole piece 30 may also be a positive pole piece. Along the first direction x, the outermost side of the battery cell 100, that is, the outermost layer of the stacked first pole pieces 10, the diaphragm 20, and the second pole piece 30, is the first pole piece 10 or the second pole piece 30.
[0045] Along the first direction x, the peeling force between the outermost second pole piece 30 of the battery cell 100 and the outermost diaphragm 20 on the same side is F1, that is, the peeling force between the outermost diaphragm 20 of the battery cell 100 and the second pole piece 30 adjacent to the diaphragm 20 is F1.
[0046] F1 satisfies: F1 ≥ 13N / m.
[0047] By improving the peeling force between the outermost second pole piece 30 of the battery cell 100 and the separator 20, that is, improving the adhesion between the separator 20 and the second pole piece 30, the peeling force F1 between the two is ≥ 13N / m. The problem of curling and warping of the pole piece can be reduced, so that the distance between the first pole piece 10 and the second pole piece 30 will not have a gap due to curling and warping deformation, resulting in a larger interval at the interface bonding, which increases the transmission distance of lithium ions, reduces the transmission distance of lithium ions, reduces the problem of black spot lithium precipitation during the cycle of the battery cell 100, and improves the cycle life of the battery.
[0048] At the same time, since the adhesion between the diaphragm 20 and the second pole piece 30 becomes greater, the deformation problem of the battery cell 100 during the cycle can be reduced, the flatness of the battery cell 100 is improved, and the abnormal expansion in the thickness direction during the cycle is reduced, thereby improving the cycle performance of the battery.
[0049] Preferably, F1 satisfies: F1 ≥ 18 N / m.
[0050] In a possible implementation, the outermost pole piece of the battery cell 100 is a single-sided pole piece, that is, the outermost first pole piece 10 or the second pole piece 30 of the battery cell 100 has paste on only one side, and the paste side faces inward. The other pole pieces are double-sided pole pieces, that is, the first pole piece 10 or the second pole piece 30 has paste on both sides.
[0051] The outermost pole piece of the battery cell 100 is a single-sided pole piece, which reduces the thickness of the battery cell 100 and thus improves the energy density of the battery.
[0052] like Figure 1 As shown, in a possible implementation, the outermost side of the battery cell 100 is the first pole piece 10. Figure 2 As shown, in another possible implementation, the outermost side of the battery cell 100 is the second pole piece 30 .
[0053] In a possible implementation, in the battery cell 100 , the peeling force between the diaphragm 20 and the first electrode sheet 10 is smaller than the peeling force between the diaphragm 20 and the second electrode sheet 30 , that is, the bonding force between the second electrode sheet 30 and the diaphragm 20 is greater than the bonding force between the first electrode sheet 10 and the diaphragm 20 .
[0054] Preferably, the difference between the peeling force between the diaphragm 20 and the second pole piece 30 and the peeling force between the diaphragm 20 and the first pole piece 10 is greater than or equal to 4 N / m.
[0055] Since the second pole sheet 30 expands greatly during battery cycling, it is necessary to set the peeling force of the second pole sheet 30 higher so as to reduce the abnormal expansion in the thickness direction during cycling.
[0056] In one possible implementation, the peeling force between the remaining diaphragms 20 and the second pole piece 30 adjacent to the diaphragm 20 is F2, that is, except for the peeling force between the outermost diaphragm 20 of the battery cell 100 and the second pole piece 30 is F1, the peeling force between the remaining diaphragms 20 and the second pole piece 30 is F2.
[0057] F2 satisfies: F2 ≥ 15N / m.
[0058] By increasing the peeling force between the remaining second pole pieces 30 and the diaphragm 20, that is, improving the adhesion between the diaphragm 20 and the second pole piece 30 in the battery cell 100, the deformation problem of the battery cell 100 during cycling can be reduced, the flatness of the battery cell 100 is improved, and the abnormal expansion in the thickness direction during cycling is reduced, thereby improving the cycle performance of the battery. In particular, for the second pole piece 30 coated with silicon-containing material, the influence of the silicon content on the expansion can be effectively reduced, and the deformation of the second pole piece 30 can be reduced.
[0059] Preferably, F2 satisfies: F2 ≥ 20 N / m.
[0060] like Figure 3 and Figure 4 As shown, in a possible implementation, the battery cell 100 is composed of at least two electrode sheet groups of different sizes. The electrode sheet groups of different sizes are stacked to form a 3D special-shaped battery.
[0061] In a possible implementation, the battery cell 100 includes a first electrode sheet group 101 and a second electrode sheet group 102. Along a first direction x, the first electrode sheet group 101 and the second electrode sheet group 102 are stacked.
[0062] In a possible implementation, the first pole piece 10 includes a first small pole piece 11 and a first large pole piece 12 , and the second pole piece 30 includes a second small pole piece 31 and a second large pole piece 32 .
[0063] The size of the first small pole piece 11 along the second direction y is smaller than the size of the first large pole piece 12 along the second direction y, and the size of the second small pole piece 31 along the second direction y is smaller than the size of the second large pole piece 32 along the second direction y. The first small pole piece 11 and the second small pole piece 31 form a first pole piece group 101, and the first large pole piece 12 and the second large pole piece 32 form a second pole piece group 102. Therefore, along the second direction y, the size of the first pole piece group 101 is smaller than the size of the second pole piece group 102.
[0064] The second direction y is perpendicular to the first direction x.
[0065] Along the first direction x, the first pole piece group 101 and the second pole piece group 102 are stacked and bonded to each other, that is, the first pole piece group 101 and the second pole piece group 102 are bonded together.
[0066] The glue can better bond and fix the electrode groups of different sizes, thereby effectively preventing the separation of the electrode groups of different sizes and causing safety problems; and, by gluing the electrode groups of different sizes together, the levelness of the electrode groups of different sizes in the thickness direction can be ensured, and at the same time, deformation caused by different expansion forces due to different electrode sizes can be prevented, thereby improving the flatness of the battery cell 100 and improving the cycle performance of the battery.
[0067] In a possible implementation, the peeling force between the first electrode assembly 101 and the second electrode assembly 102 is F3, and F3 satisfies F3 ≥ 30 N / m.
[0068] A larger peeling force can improve the safety performance of the battery cell 100 and prevent the first electrode assembly 101 from being separated from the second electrode assembly 102 during a drop process, thereby preventing safety problems caused.
[0069] In one possible implementation, along the first direction, the difference between the peeling force between the pole pieces in the overlapping area of the second pole piece group 102 and the first pole piece group 101, and the peeling force between the pole pieces in the separately stacked area of the second pole piece group 102, is less than or equal to 50% of the smaller value of the two. Preferably, the difference between the two is less than or equal to 40% of the smaller value of the two.
[0070] In a possible implementation, along the first direction x, both sides of the first pole piece group 101 are first small pole pieces 11 , and both sides of the second pole piece group 102 are first large pole pieces 12 .
[0071] In another possible implementation, along the first direction x, both sides of the first pole piece group 101 are second small pole pieces 31 , and both sides of the second pole piece group 102 are second large pole pieces 32 .
[0072] In one possible implementation, along the second direction y, one end of the first pole piece group 101 is aligned with one end of the second pole piece group 102, that is, along the second direction y, one end of the first small pole piece 11 is aligned with one end of the first large pole piece 12, and one end of the second small pole piece 31 is aligned with one end of the second large pole piece 32.
[0073] In one possible implementation, along the first direction x, the peeling force between the outermost diaphragm 20 in the first pole piece group 101 and the second small pole piece 31 adjacent to the diaphragm 20 is F4, and the peeling force between the outermost diaphragm 20 in the second pole piece group 102 and the second large pole piece 32 adjacent to the diaphragm 20 is F5.
[0074] F4 and F5 meet the following requirements: F4 ≥ 13 N / m; F5 ≥ 13 N / m.
[0075] By improving the peeling force between the outermost second small electrode sheet 31 or the second large electrode sheet 32 of the first electrode sheet group 101 and the second electrode sheet group 102 and the diaphragm 20, the adhesion between the diaphragm 20 and the second small electrode sheet 31 or the second large electrode sheet 32 is improved, which can reduce the curling and warping problems of the outermost electrode sheets in the first electrode sheet group 101 and the second electrode sheet group 102, reduce the gaps at the interface bonding, and reduce the phenomenon that the interval becomes larger, the transmission distance of lithium ions becomes longer, and the transmission distance of lithium ions is reduced, thereby reducing the problem of black spot lithium precipitation in the first electrode sheet group 101 and the second electrode sheet group 102 during the cycle, and improving the cycle life.
[0076] At the same time, since the adhesion between the diaphragm 20 and the second small electrode piece 31 or the second large electrode piece 32 becomes greater, the deformation problem of the first electrode piece group 101 and the second electrode piece group 102 during the cycle can be reduced, the overall flatness of the battery cell 100 is improved, and the abnormal expansion in the thickness direction during the cycle is reduced, thereby improving the cycle performance of the battery.
[0077] Preferably, F4 and F5 satisfy: F4 ≥ 18 N / m; and / or F5 ≥ 18 N / m.
[0078] like Figure 5 As shown, in a possible implementation, along the second direction y, the peeling force at each position when the diaphragm 20 and the second pole piece 30 are peeled off is a, the average value of the peeling force between the diaphragm 20 and the second pole piece 30 is b, and a and b satisfy: 50%b≤a≤150%b. That is, it is ensured that when peeling along the second direction y, the peeling force fluctuates between ±50% of the average value.
[0079] 50%b≤a≤150%b can ensure that the peeling force of the second pole piece 30 at each position along the second direction y is not much different, thereby preventing the occurrence of black spots and lithium deposition in a local area of the second pole piece 30, which in turn causes the problem of cycle failure.
[0080] During the test, a distance of 6 mm is removed from both ends of the second pole piece 30 along the second direction y to prevent interference.
[0081] In a possible implementation, along the third direction, the peeling force at each position when the diaphragm 20 and the second pole piece 30 are peeled off is c, the average value of the peeling force between the diaphragm 20 and the second pole piece 30 is d, and c and d satisfy: 50% d ≤ c ≤ 150% d. That is, it is ensured that when peeling along the third direction, the peeling force fluctuates between ±50% of the average value.
[0082] The third direction is perpendicular to the first direction x and the second direction y.
[0083] 50% d≤c≤150% d can ensure that the peeling force of the second pole piece 30 at each position along the third direction is not much different, thereby preventing the occurrence of black spots and lithium deposition in a local area of the second pole piece 30, which in turn leads to cycle failure.
[0084] During the test, a distance of 6 mm is removed from both ends of the second pole piece 30 along the third direction to prevent interference.
[0085] In a possible implementation, the first pole piece 10 includes a first current collector 13 and a first active material layer 14 located on at least one side of a surface of the first current collector 13 .
[0086] When the outermost portion of the battery cell 100 along the first direction x is the first pole piece 10 , the first pole piece 10 includes a first current collector 13 and a first active material layer 14 located on one side of the surface of the first current collector 13 .
[0087] In a possible implementation, the second pole piece 30 includes a second current collector 33 and a second active material layer 34 located on at least one side of a surface of the second current collector 33 .
[0088] When the outermost side of the battery cell 100 along the first direction x is the second pole piece 30 , the second pole piece 30 includes a second current collector 33 and a second active material layer 34 located on one side of the surface of the second current collector 33 .
[0089] In a possible implementation, the second active material layer 34 includes a graphite-doped silicon material.
[0090] In a possible implementation, the silicon content of the second active material layer 34 is x, and the peeling force between the second pole piece 30 and the diaphragm 20 is y.
[0091] x and y satisfy: y ≥ 11*x+13.
[0092] The peeling force of the second pole piece 30 is positively correlated with the silicon content of the second active material layer 34. The higher the silicon content in the second active material layer 34, the greater the expansion and the greater the possibility of deformation of the second pole piece 30. Therefore, a higher peeling force is required to suppress the deformation of the second pole piece 30.
[0093] For example, if the silicon content in the second active material layer 34 is 5%, the peeling force of the second electrode sheet 30 needs to be y≥13.55 N / m.
[0094] In addition, the embodiment of the present application further provides a battery 200 , including a housing 201 and a battery cell 100 . The battery cell 100 is disposed in the housing 201 .
[0095] In a possible implementation, along the first direction x, the outermost first pole piece 10 or the second pole piece 30 of the battery cell 100 is in direct contact with the housing 201 .
[0096] The battery cell 100 is in direct contact with the shell 201. Compared with fixing with glue, in the first direction x, since the adhesive layer in the shell 201 is reduced, the design thickness of the shell 201 can be reduced, thereby reducing the thickness of the battery 200 and improving the energy density of the battery 200. In addition, the surface of the battery cell 100 is a flat large electrode surface, and no glue is applied, which can improve the flatness of the battery 200, reduce the possibility of gaps at the interface due to expansion in the thickness direction during charging and discharging, and improve the long cycle performance of the battery 200.
[0097] In a possible implementation, the surface flatness of the battery 200 is less than or equal to 0.3 mm.
[0098] The higher the flatness of the battery 200 is, the more favorable it is to the cycle performance of the battery 200 , and the longer the cycle life of the battery 200 is.
[0099] Preferably, the surface flatness of the battery 200 is less than or equal to 0.2 mm.
[0100] In a possible implementation, the housing 201 is made of an aluminum-plastic film housing.
[0101] In a possible implementation, the battery 200 further includes a tab 202 . The tab 202 is used to connect to the first pole piece 10 or the second pole piece 30 in the battery cell 100 .
[0102] The second direction y is perpendicular to the first direction x, and the third direction z is perpendicular to the first direction x and the second direction y. The tab 202 extends out of the housing 201 along the third direction z.
[0103] like Figure 6As shown, the method for testing the flatness of the battery 200 is: using a 3D profilometer to scan the flatness test area on the surface of the battery 200, so as to measure the flatness of the surface of the battery 200.
[0104] The test area on the surface of the battery 200 needs to avoid the four sides of the battery 200, so as to prevent the tab 202 and the chamfered area of the electrode in the battery 200 from affecting the test results.
[0105] Specifically, along the second direction y, the widths of the areas on both sides of the battery 200 to be avoided are A1 and A2 respectively, and along the third direction z, the widths of the areas on both sides of the battery 200 to be avoided are A3 and A4 respectively. The sizes of A1, A2, A3, and A4 are: A1 = 4 mm, A2 = 4 mm, A3 = 8 mm, and A4 = 4 mm respectively.
[0106] A3 is an area of the battery 200 close to the tab 202 along the third direction z, and A4 is an area of the battery 200 away from the tab 202 along the third direction z.
[0107] Among them, the battery 200 is not limited to lithium batteries, and the technology may be applied to sodium batteries in the future. Lithium-ion batteries are preferred in the present embodiment. It should be noted that the preparation process of lithium-ion batteries is as follows:
[0108] Step 1: Preparation of positive electrode sheet: Prepare positive electrode active material slurry, mix the conductive agent and PVDF glue evenly, then add lithium cobalt oxide and stir evenly to obtain positive electrode active material layer slurry. Coat the positive electrode active material on the surface of aluminum foil, bake, roll and cut to obtain positive electrode sheet.
[0109] The positive electrode active material layer is composed of 97.6% by mass of lithium cobalt oxide, 1.05% by mass of PVDF, and 1.35% by mass of a conductive agent, wherein the conductive agent is composed of conductive carbon black, single-walled carbon nanotubes, and multi-walled carbon nanotubes.
[0110] Step 2: Preparation of negative electrode sheet: Prepare negative electrode active material slurry, mix 0.5% by mass of conductive agent and 97% by mass of graphite powder, then add deionized water, 1.3% by mass of carboxymethyl cellulose and 1.2% by mass of styrene-butadiene rubber adhesive, stir evenly, and obtain negative electrode active material layer slurry. Coat the negative electrode active material slurry on carbon-coated copper foil, bake, roll and cut to obtain negative electrode sheet.
[0111] Step 3: The positive and negative electrodes are die-cut and laminated to obtain electrode groups. Electrode groups of different sizes are stacked together to form a battery cell.
[0112] Step 4: The aluminum-plastic film is punched through the mold core to obtain the film shell.
[0113] Wherein, the thickness of the aluminum-plastic film shell is 30μm-200μm.
[0114] Step 5: After the battery cell is placed in the membrane shell, it is packaged, baked, injected, formed, sorted, sealed again, OCV (open circuit voltage) and packaged to obtain a lithium-ion battery.
[0115] The electrolyte is a commercially available conventional electrolyte, and the lithium salt therein is LiFP6.
[0116] It can be understood that the active material of the positive electrode active material layer may include one or more of lithium cobalt oxide, lithium iron phosphate, nickel cobalt manganese lithium, nickel cobalt aluminum lithium, lithium manganese oxide and lithium-rich manganese-based lithium.
[0117] The negative electrode active material layer may include one or more of natural graphite, artificial graphite, mesophase carbon microbeads, lithium titanate, silicon negative electrode, silicon-carbon negative electrode and alloy negative electrode.
[0118] The positive electrode adhesive is mainly polyvinylidene fluoride (PVDF) adhesive, and the negative electrode adhesive is mainly styrene-butadiene rubber. The conductive agent includes at least one of conductive carbon black, Ketjen black, single-walled carbon nanotubes, and multi-walled carbon nanotubes.
[0119] It should be noted that the following is a table of cycle performance tests on the batteries of the examples.
[0120] Table 1 is the test data table of normal temperature and high temperature cycle of the embodiment
[0121] Normal temperature cycle High temperature cycle Cycle times 1600T 800T Capacity retention rate More than 80% More than 80% Recovery capacity retention rate More than 97% More than 97% Thickness expansion Within 11% Within 11%
[0122] Among them, the lithium-ion battery is subjected to cycle testing, and the cycle expansion and capacity retention rate are paid attention to during the cycle testing, especially the junction between the large and small electrode groups.
[0123] The specific cycle performance test method is as follows:
[0124] 1. Under normal temperature conditions
[0125] 1. Take a 50% SOC battery and use a 600g±20g PPG thickness gauge to test the initial thickness (T0) of the battery;
[0126] 2. Let the battery stand for 10 minutes at 25℃±3℃, discharge to 3.0V at 0.2C, let stand for 10 minutes, charge to 4.50V at 0.5C constant current, charge at 4.50V constant voltage, cut-off current 0.02C, let stand for 10 minutes, and use 600g±20gPPG thickness gauge to test the battery thickness (Ta), (Ta / T0-1)*100% full charge thickness expansion rate; discharge to 3.0V at 0.2C, let stand for 10 minutes, and record the initial capacity C0 of the battery;
[0127] 3. Cycle: At 25℃±3℃, charge the battery at 2.0C constant current to 4.25V, charge at 4.25V constant voltage with a cut-off current of 1.0C, charge at 1.0C constant current to 4.50V, charge at 4.50V constant voltage with a cut-off current of 0.3C; discharge at 0.7C constant current to 3.0V; cycle once according to the above charge and discharge mechanism, record the capacity C1 once, and the capacity retention rate is: C1 / C0*100%; continue cycling;
[0128] 4. After every 100T, charge at 0.5C constant current to 4.50V at 25℃±3℃, charge at 4.50V constant voltage, cut-off current 0.02C, let stand for 10min, and use 600g±20gPPG thickness gauge to test battery thickness (Tb), (Tb / T0-1)*100% thickness expansion rate; discharge at 0.2C to 3.0V, let stand for 10min, record the battery recovery capacity Ca; battery recovery capacity retention rate Ca / C0*100%.
[0129] 2. Under high temperature conditions
[0130] 1. Take a 50% SOC battery and use a 600g±20g PPG thickness gauge to test the initial thickness (T0) of the battery;
[0131] 2. Let the battery stand for 10 minutes at 45℃±3℃, discharge to 3.0V at 0.2C, let stand for 10 minutes, charge to 4.50V at 0.5C constant current, charge at 4.50V constant voltage, cut-off current 0.02C, let stand for 10 minutes, and use 600g±20gPPG thickness gauge to test the battery thickness (Ta), (Ta / T0-1)*100% full charge thickness expansion rate; discharge to 3.0V at 0.2C, let stand for 10 minutes, and record the initial capacity C0 of the battery;
[0132] 3. Cycle: At 45℃±3℃, charge the battery at 2.0C constant current to 4.25V, charge at 4.25V constant voltage with a cut-off current of 1.0C, charge at 1.0C constant current to 4.50V, charge at 4.50V constant voltage with a cut-off current of 0.5C; discharge at 0.7C constant current to 3.0V; cycle once according to the above charge and discharge mechanism, record the capacity C1 once, and the capacity retention rate is: C1 / C0*100%; continue cycling;
[0133] 4. After every 100T, charge at 0.5C constant current to 4.50V at 25℃±3℃, charge at 4.50V constant voltage, cut-off current 0.02C, let stand for 10min, and use 600g±20gPPG thickness gauge to test battery thickness (Tb), (Tb / T0-1)*100% thickness expansion rate; discharge at 0.2C to 3.0V, let stand for 10min, record the battery recovery capacity Ca; battery recovery capacity retention rate Ca / C0*100%.
[0134] The following is the method for testing the peeling force of the battery cells in this application:
[0135] The peeling force between the outermost negative electrode sheet and the separator
[0136] Take the battery cell and discharge it to 3.0V for disassembly; according to the stacking method of the battery cell, disassemble it to the following interfaces, m: single-sided positive electrode sheet & diaphragm + negative electrode sheet & remaining electrode sheet, or m: single-sided negative electrode sheet + diaphragm & remaining electrode sheet; peel the substrate m with a universal tensile machine to separate it from other layers. Equipment operating conditions: stroke 45mm, operating speed 20mm / min; the average peeling force obtained during the test process is the peeling force between the outermost negative electrode sheet and the diaphragm.
[0137] The peeling force between other layers of negative electrode and separator
[0138] Take the battery cell and discharge it to 3.0V for disassembly; disassemble it to the following interface, n: other layers of negative electrode sheets + diaphragm & remaining electrode sheets; peel the substrate n with a universal tensile machine to separate it from the diaphragm & remaining electrode sheets. Equipment operating conditions: stroke 45mm, operating speed 20mm / min; the average peeling force obtained during the test process is the peeling force between the other layers of negative electrode sheets and the diaphragm.
[0139] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.
Claims
1. A battery cell, characterized in that: The invention comprises a first pole piece (10), a diaphragm (20) and a second pole piece (30); a plurality of the first pole pieces (10) and the second pole pieces (30) are stacked along a first direction, and the diaphragm (20) is arranged between adjacent first pole pieces (10) and second pole pieces (30); The first pole piece (10) comprises a first small pole piece (11) and a first large pole piece (12); the second pole piece (30) comprises a second small pole piece (31) and a second large pole piece (32); the size of the first small pole piece (11) along the second direction is smaller than the size of the first large pole piece (12) along the second direction; the size of the second small pole piece (31) along the second direction is smaller than the size of the second large pole piece (32) along the second direction; the second direction is perpendicular to the first direction; the first small pole piece (11) and the second small pole piece (31) form a first pole piece group (101); the first large pole piece (12) and the second large pole piece (32) form a second pole piece group (102); along the first direction, the first pole piece group (101) and the second pole piece group (102) are stacked; Along the first direction, the peeling force between the outermost diaphragm (20) and the second pole piece (30) adjacent to the diaphragm (20) is F1, and F1 satisfies: F1≥13N / m.
2. The battery cell according to claim 1, characterized in that: F1 satisfies: F1 ≥ 18 N / m.
3. The battery cell according to claim 1, characterized in that: The peeling force between the diaphragm (20) and the first pole piece (10) is smaller than the peeling force between the diaphragm (20) and the second pole piece (30).
4. The battery cell according to claim 3, characterized in that: The difference between the peeling force between the diaphragm (20) and the second pole piece (30) and the peeling force between the diaphragm (20) and the first pole piece (10) is greater than or equal to 4 N / m.
5. The battery cell according to claim 1, characterized in that: Along the first direction, the difference between the peeling force between the pole pieces in the overlapping area of the second pole piece group (102) and the first pole piece group (101) and the peeling force between the pole pieces in the separately stacked area of the second pole piece group (102) is less than or equal to 50% of the smaller value of the two.
6. The battery cell according to claim 5, characterized in that: Along the first direction, the difference between the peeling force between the pole pieces in the overlapping area of the second pole piece group (102) and the first pole piece group (101) and the peeling force between the pole pieces in the separately stacked area of the second pole piece group (102) is less than or equal to 40% of the smaller value of the two.
7. The battery cell according to claim 1, characterized in that: The peeling force between the first pole piece group (101) and the second pole piece group (102) is F3, and F3 satisfies F3≥30N / m.
8. The battery cell according to claim 7, characterized in that: Along the first direction, the peeling force between the outermost diaphragm (20) in the first pole piece group (101) and the second small pole piece (31) adjacent to the diaphragm (20) is F4, and the peeling force between the outermost diaphragm (20) in the second pole piece group (102) and the second large pole piece (32) adjacent to the diaphragm (20) is F5, and F4 and F5 satisfy: F4 ≥ 13 N / m; and / or F5 ≥ 13 N / m.
9. The battery cell according to claim 1, characterized in that: Along the second direction, the peeling force at each position when the diaphragm (20) and the second pole piece (30) are peeled off is a, and the average value of the peeling force between the diaphragm (20) and the second pole piece (30) is b. Along the third direction, the peeling force at each position when the diaphragm (20) and the second pole piece (30) are peeled off is c, and the average value of the peeling force between the diaphragm (20) and the second pole piece (30) is d. The second direction is perpendicular to the first direction, and the third direction is perpendicular to the first direction and the second direction. a, b, c, and d satisfy: 50% b≤a≤150% b; and / or 50% d≤c≤150% d.
10. The battery cell according to claim 1, characterized in that: The second pole piece (30) comprises a second current collector (33) and a second active material layer (34) located on at least one side of the surface of the second current collector (33), the silicon content of the second active material layer (34) is x, the peeling force between the second pole piece (30) and the diaphragm (20) is y, and x and y satisfy: y≥11*x+13.
11. A battery, characterized in that: It comprises a shell (201) and the battery cell (100) according to any one of claims 1 to 10, wherein the battery cell (100) is arranged in the shell (201).
12. The battery according to claim 11, characterized in that Along the first direction, the outermost first pole piece (10) or the second pole piece (30) is in direct contact with the housing (201).
Citation Information
Patent Citations
Laminated battery cell and lithium ion battery
CN112271299A
Lithium ion battery
CN112563665A
Diaphragm and battery containing diaphragm
CN114006024A
Winding type battery cell
CN115064783A
Battery cell and battery
CN117352812A
Cited By
Secondary battery and electric device
WO2026188501A1
Battery cell and electrical device
WO2026189317A1
Secondary battery and electric device
WO2026193750A1
